Examining implementation and labor market outcomes of targeted transit subsidies: Subsidy by sistema nacional de selección de beneficiarios for urban poor in Bogotá, Colombia (2016)
To meet the challenges of providing affordable public transit service without compromising the financial sustainability of the system, many transit systems are setting fares at cost-recovery levels. However, to offer affordable transport service for the urban poor, cities can provide targeted subsidies. Bogotá, Colombia, has implemented a pro-poor public transit subsidy scheme that leverages the adoption of smart cards in its new public transit system and the country's poverty-targeting instruments. This study presents a critical analysis of the rationale, design, and implementation of Bogotá's public transit subsidy. On the basis of this experience, two research questions were explored: What are the determinants of the user's self-selection? What are the causal links between the subsidy and labor market outcomes of employment and income? Two regressions (linear and probabilistic) were used to identify the characteristics of individuals who choose to request the subsidized fare. A quasi-experimental technique was used for the impact assessment of the subsidy on labor market outcomes. This research allows an understanding of how to design targeted subsidies for maximum labor market outcomes.